STUDENTS' READING COMPREHENSION USING LISTEN–READ–DISCUSS (LRD) STRATEGY - Lasim Muzammil (JURNAL ILMIAH BAHASA DAN SASTRA, 2020)
The goal of this article is to review studies that investigated the Listen–Read– Discuss (LRD) strategy towards students’ reading comprehension. In understanding the meaning from a passage, the reader wants a good strategy for comprehension. There were varieties of reading strategies developed by experts all around the world, but the researcher focused on one of the strategies called the L–R–D strategy. L–R–D is a strategy that introduces students’ prior knowledge before they start reading, during, and after reading by seeing the teacher’s lecture, reading a selected text, and discuss it with their classmates. L–R–D may help students convey the author’s messages with their own words, increase their comprehension, and also help students to remember what they read. The L–R–D strategy could be beneficial as it is an engaging strategy for readers who are struggling with reading comprehension. Because the materials are done orally, students who are not able to read the whole passage at least can understand a little information from the passage. For students who have low proficiency in background knowledge about the reading passage, they could obtain through the listening phase where after that they could comprehend the passage in the reading phase.